2016
DOI: 10.1111/jade.12104
|View full text |Cite
|
Sign up to set email alerts
|

Imitative or Iconoclastic? How Young Children use Ready‐Made Images in Digital Art

Abstract: Digital art‐making tends to foreground the inclusion of ready‐made images in children's art. While some lament children's use of such images, suggesting that they constrain creativity and expression, others have argued that ready‐made digital materials offer children the opportunity to create innovative and potentially iconoclastic artefacts through processes of ‘remix’ and ‘mash‐up’. In order to further this debate, observations are needed to explore the different ways that children use ready‐made images in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In contrast, art educators often implement the term ‘meaning‐making’ to differentiate between pedagogic approaches: those that foster pupils’ articulation of purpose through art production, in comparison to pedagogy more concerned with skill acquisition and learning outcomes (Sakr et al . ). It refers to children's intentionality when making art, not simply replicating images or regurgitating processes demonstrated by the teacher (Malin ).…”
Section: Meaning‐makingmentioning
confidence: 97%
See 3 more Smart Citations
“…In contrast, art educators often implement the term ‘meaning‐making’ to differentiate between pedagogic approaches: those that foster pupils’ articulation of purpose through art production, in comparison to pedagogy more concerned with skill acquisition and learning outcomes (Sakr et al . ). It refers to children's intentionality when making art, not simply replicating images or regurgitating processes demonstrated by the teacher (Malin ).…”
Section: Meaning‐makingmentioning
confidence: 97%
“…For example, meaning‐based art pedagogies often refer to experimentation with media properties and the meanings they embody (Pringle ; Malin ; Sakr et al . ). This involves developing aesthetic intentions through an intertextual dialogue between maker and media (Addison ), focusing on creation through reflection (Pringle ) and formulating imaginative, inventive responses (Malin ; Sakr et al .…”
Section: Meaning‐makingmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, it is insightful to return to the classic study of Labbo (1996), which, more than 20 years ago, demonstrated that when kindergarteners engage in art-making on a computer (as opposed to on paper), they show greater flexibility in their approach to the art-making, and are just as likely to use the computer screen as a ‘playground’ or ‘stage’ as they are to use the screen as a basic ‘canvas’. My own research in this area (Sakr, 2016; Sakr et al, 2016a, 2016b) has suggested that children’s digital art-making is often characterised by a quicker pace and a more relaxed sense of ownership.…”
Section: Children’s Art-making With Different Semiotic Resourcesmentioning
confidence: 99%